2020
DOI: 10.1186/s13059-020-02190-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase epsilon is required for heterochromatin maintenance in Arabidopsis

Abstract: Background Chromatin organizes DNA and regulates its transcriptional activity through epigenetic modifications. Heterochromatic regions of the genome are generally transcriptionally silent, while euchromatin is more prone to transcription. During DNA replication, both genetic information and chromatin modifications must be faithfully passed on to daughter strands. There is evidence that DNA polymerases play a role in transcriptional silencing, but the extent of their contribution and how it rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 83 publications
3
29
0
Order By: Relevance
“…S4 ). Our observations are consistent with recent publications where an increase in H3K9me2 and H3K27Ac marks was observed in the atxr5/6 (W) mutant ( 17 , 18 ). Although we cannot rule out that other untested epigenetic marks may be involved, these data suggest that loss of H3K27me1 is the major contributor to the chromocenter decompaction phenotype observed in atxr5/6 (W) mutants.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…S4 ). Our observations are consistent with recent publications where an increase in H3K9me2 and H3K27Ac marks was observed in the atxr5/6 (W) mutant ( 17 , 18 ). Although we cannot rule out that other untested epigenetic marks may be involved, these data suggest that loss of H3K27me1 is the major contributor to the chromocenter decompaction phenotype observed in atxr5/6 (W) mutants.…”
Section: Resultssupporting
confidence: 94%
“…In particular, it seems possible that some form of genome instability or replication stress occurs in atxr5/6 (W), causing induction of DNA damage response genes. Indeed, similar sets of DNA damage genes are also activated in mutants of genes involved in DNA replication, such as in FAS1 and FAS2 , both components of the chromatin assembly factor 1 (CAF-1) chaperone complex, as well as in BRU1 , RFC1 , and mutations in DNA polymerases, Pol alpha (α), delta (δ), and epsilon (ε) ( 17 , 26 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…TEs found in the pericentromeric heterochromatin are heavily methylated. In a recent study, Bourguet and his colleagues have noted that the significant release of heterochromatin silencing in AtPOL2A gene mutants is due to increased levels of DNA methylation and histone H3 lysine 9 methylation, and thus AtPOL2A is important to maintain heterochromatin structure and function [29]. Consistent with previous studies, we also observed that the silencing of the majority of pericentromeric TEs are released in atpol2a-1 mutant.…”
Section: Discussionsupporting
confidence: 91%
“…Our PPI analysis also showed that uncharacterized AT3G49160 interacts with FER1; both of these genes are known to be expressed in response to hydrogen peroxide [26][27][28]. AtPOL2A is important to maintain heterochromatin structure and function [29].…”
Section: Transcriptome Analysis Of Atpol2 Gene Mutantsmentioning
confidence: 64%
“…Chromatin density is key to transcriptional activity as it determines access of the transcriptional machinery to DNA. Heterochromatic regions are tightly packed and transcriptionally silent regions that are typically associated with repetitive sequences and TEs, whereas euchromatin is less dense and enriched with transcriptionally active genes (Bourguet et al, 2020). Chromatin density is dependent on the distribution of nucleosomes, each of which consists of two copies of four histone proteins (H2A, H2B, H3, H4), wrapped by c. 147 bp of DNA (Luger et al, 1997) and connected by variable stretches of internucleosomal DNA associated with linker H1 histones (Rutowicz et al, 2019).…”
Section: Plant Epigenetics: An Overview Of the Main Mechanismsmentioning
confidence: 99%